One year experience at the Emergency Unit of the Children’s Hospital of Parma - Giacalone, T.; Vanelli, M.; Zinelli, et al., C. (Acta Biomedica Atenei Parmensis, 2003)
The objective of the study was to analyse the activity of the Paediatric Emergency Unit (PEU) of the Children’s Hospital in Parma, Italy, in the first year of its functioning. To this aim, the child’s chronological age, place of origin (town or province), ethnic group, cause of consultation, time and date of admission, diagnosis and final destination were retrospectively collected from the clinical notes of all children who attended PEU from 1st. 10.1998 to 30th. 09.1999. During the period of this study 8,564 medical consultations (57% of users were male) were carried out by the Paediatricians on duty in the EU of The Children’s Hospital. The average age of the patients was 3.9±3.5 years. Only 7% of patients passed through the General Emergency Department of the same Hospital. The peak period of consultations was found to be in February. The number of daily attendances progressively increased from Monday to Sunday according to a r of 0.59 (p